2017
DOI: 10.11114/jets.v5i3.2209
|View full text |Cite
|
Sign up to set email alerts
|

The Role of University Students’ General Self-Efficacy, Depression and Psychological Well-being in Predicting Their Exercise Behavior

Abstract: The aim of this research is to examine the relationship between exercise and general self-efficacy, depression, and psychological well-being of college students. Five hundred and twenty-two university students (n male= 273; X age = 23.33±4.36 and n female = 279; X age =25.91±7.11) have participated in this research. The General Self-Efficacy Scale (GSES), Beck Depression Inventory (BDI), Physical Activity Stages of Change Questionnaire (PASCQ), and "Psychological Well-Being Scale (PWBS) have been applied to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…This may be owing to those who exercised regularly were only aware that exercise was a healthy lifestyle, this good habit did not affect their awareness of breast cancer screening. By conducting a survey among university students, Gözde Ersöz found that students in the maintenance phase of physical exercise had higher self‐efficacy level than those in the exercise preparation stage . We should encourage the college students to form the habit of exercise after entering the university.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be owing to those who exercised regularly were only aware that exercise was a healthy lifestyle, this good habit did not affect their awareness of breast cancer screening. By conducting a survey among university students, Gözde Ersöz found that students in the maintenance phase of physical exercise had higher self‐efficacy level than those in the exercise preparation stage . We should encourage the college students to form the habit of exercise after entering the university.…”
Section: Discussionmentioning
confidence: 99%
“…By conducting a survey among university students, Gözde Ersöz found that students in the maintenance phase of physical exercise had higher self-efficacy level than those in the exercise preparation stage. 35 We should encourage the college students to form the habit of exercise after entering the university.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to these results, previous studies of the same nature also found a positive relationship between regular exercise and general self-efficacy [29,30]. Research has found that those who exercise and show continuity in exercise positively affects psychological phenomena like self-efficacy and psychological well-being, while not engaging in exercise or not considering exercise has a positive relation with depression [21]. This is very important considering health science student require stable psychological wellbeing to be able to study.…”
Section: Discussionmentioning
confidence: 50%
“…physical activity [18,21,25,27]. According to social cognitive theory, the study showed that self-efficacy (individual factor) explained part of the association between barriers to physical activity (environmental factors) and health behaviour intentions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation